PENERAPAN PERMAINAN KECIL BENTENG-BENTENGAN UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN PJOK DI SMK HARAPAN BANGSA KOTA SERANG - Ade Restu Maulana; Desty Subroto; Muhamad Saeza; Nadya Rahayu; Ahmad Hujaimi; Reva Anwar Marsela (CV. Denasya Smart Publisher, 2025)
Learning is a system that involves an integrated set of interrelated and interactive components to achieve expected results optimally, with predefined goals. Physical Education, Sports, and Health (PJOK), for example, encourages students to move actively to reach the goal of improved physical fitness. PJOK does not require students to always be able and skilled at practicing the material; rather, it emphasizes the willingness, desire, and success in actively moving or participating in learning activities. Active participation can increase when the learning process is engaging, exciting, non-monotonous, innovative, and creative. This can be achieved by incorporating small games, such as the traditional